When Higher Incomes Reduce Welfare: Queues, Labor Supply, and Macro Equilibrium in Socialist Economies - Boycko, M. (Quarterly Journal of Economics, 1992)
Starting from a micro model of consumer behavior under rationing by queuing that utilizes Gary Becker's "Allocation of Time" framework, we develop a simple macroeconomic model of a socialist economy. The "length of the queue" is the key endogenous variable that equilibrates aggregate supply and aggregate demand. Comparative statics analysis shows that an increase in wages over money prices brings about longer queues that reduce labor supply, output, and welfare. When shortages grow beyond a certain critical level, queues fail to sustain aggregate equilibrium in the economy.